Relationships between internal and external load measures and fitness level changes in professional soccer players - Martin, M.; Rampinini, E.; Bosio, A.; Azzalin, A.; McCall, A.; Ward, P. (Research Quarterly for Exercise and Sport, 2023)
Purpose Understanding the dose-response relationship between internal and external training load with changes in aerobic fitness and intermittent running capacity, during different periods of the season, may help in optimizing training process. The aim of the present study was to investigate the dose-response relationships between load measures and changes in aerobic fitness and intermittent running capacity among a large cohort of professional soccer players.